Reforming pensions principles and policy choices - Barr, N. A.; Diamond, Peter A. (New York ; Oxford : Oxford University Press, 2008)
Mandatory pensions are a worldwide phenomenon. However, with fixed contribution rates, monthly benefits, and retirement ages, pension systems aren't consistent with three long-run trends: declining mortality and fertility, and earlier retirement. Many systems need reform. This book explains the economics of pension design.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Pensions; Pension trusts; Pensions -- Chile; Pensions -- China